Effect of tillage systems on yield and its components of seven cowpea (Vigna unguiculata L.) varieties and performing correlation, path and cluster analysis under Sulaimani condition - Abdulkhaleq, Dana Azad; Hama-Umin, Bestoon Omer; Khorshid, Fawzy Faidhullah; Hama-Ali, Emad Omer (Sulaimani Journal for Pure and Applied Sciences, 2018)
This study was conducted during 2015 season at The Qlyasan Agricultural Research Station / College of Agricultural Sciences / University of Sulaimani. Randomized Complete Block Design (RCBD) with three replicates was used to study the effect of two tillage systems using (Mould board plow and Disc plow) on seven cowpea varieties (Vigna unguiculata L.) in term of agro-morphological characters and yield assessment. Mean comparisons were performed by the least significant difference test (L.S.D) at 1% and 5% levels of significance. Correlation and path coefficient analyses were performed to determine the degree of association of characters with yield and also among themselves and to detect the relative importance of the characters contributing to grain yield. Cluster analysis based on (UPMAG) was implemented to identify the genetic diversity of the genotypes. The results of this study confirm that plowing with mould board recorded the maximum values for all of the studied characters which indicate the effectiveness of this system compared to disc plow. Tropicana variety achieved the best values for most of the studied characters, while Ramshorn using mould board plow gave the highest values for the character root length and number of branches per plant respectively. Grain yield per plant were recorded highly significant positive correlations with Pod yield/plant, number of pods per plant, pod length with 0.978, 0.766, and 0.755 respectively, while significant positive correlation was noticed between grain yield per plant and pod weight and 100-grain weight with 0.560 and 0.541 respectively. Maximum positive direct effect in grain yield recorded by pod yield per plant with 0.906, while maximum positive indirect effect in grain yield recorded by number of pods per plant via pod yield per plant with 0.771. Cluster analysis indicated three groups in both tillage systems depending on the agro-morphological data with a small differences because (American Cowpea) genotype was in first group in mould board plow and in second groups in disc plow tillage systems results indicated the presence of high variability between genotypes in both tillage systems.
Keywords: Cowpea Genotypes; Grain yield; Correlation Analysis; Path Coefficient Analysis and Cluster Analysis